The use of ash of thermal power plants in mortar mixtures and concrete - Rakhimov Shavkat Turdimurotovich; Babakulova Nilufar Bahramjanovna (Research Parks Publishing LLC, 2020)
Our research is devoted to the issue of using waste from the mining industry (waste rock sand, waste from the mining and processing of marble), the energy industry (fly ash from thermal power plants), the copper smelting industry (copper smelting slags) in the preparation of filling mixtures used for filling the worked-out space in underground mining works.